Prior Upper Body Exercise Impairs 4-km Cycling Time-Trial Performance Without Altering Neuromuscular Function - Bertuzzi, Romulo (2020)
Purpose: This study investigated the effects of previous exhaustive upper body exercise on performance and neuromuscular fatigue following a 4-km cycling time-trial (4-km TT). Methods: Eight recreational cyclists performed a 4-km TT with (ARMPRE) or without (CONTR) a previous arm-crank maximal incremental test. In each experimental session, neuromuscular fatigue was evaluated with a series of electrically evoked and maximal voluntary isometric contractions (MVC). Oxygen uptake ((Formula presented.) O2), heart rate, electromyographic muscle activity (EMGRMS) and rating of perceived exertion (RPE) were also recorded throughout the 4-km TT. Results: The average power output during the 4-km TT was reduced (P =.027) for the ARMPRE (299 ± 59 W) group, compared with CONTR (310 ± 59 W) and overall performance in 4-km TT was impaired (P =.021) in ARMPRE (382 ± 28 s) compared with CONTR (376 ± 27 s). The decrease observed in MVC (P =.033) and potentiated peak twitch force (P =.004) at post-TT were similar between the ARMPRE and CONTR conditions (P =.739 and P =.493, respectively). There was no (P =.619) change in voluntary activation at post-TT between conditions. (Formula presented.) O2, EMGRMS and RPE measured throughout the 4-km TT were not significantly different between the conditions (P =.558, P =.558 and P =.940, respectively). The rate of RPE change relative to power output average and heart rate was higher (P =.030 and P =.013, respectively) in ARMPRE (0.031 ± 0.018 AU/W and 168 ± 8 bpm) than CONTR (0.022 ± 0.010 AU/W and 161 ± 7 bpm). Conclusion: These results suggest that impaired performance in ARMPRE was mostly due to pronounced perception of effort rather than neuromuscular fatigue.